Effect of Fe3O4 nanoparticles on microbial diversity and biogas production in anaerobic digestion of crude glycerol - Boscaro, Mateus Eugenio [UNESP]; Canaver Marin, Danieli Fernanda [UNESP]; Camila da Silva, Daiana [UNESP]; Maintinguer, Sandra Imaculada [UNESP] (Elsevier, 2022)
This study investigated the effects of citrate-coated Fe3O4 nanoparticles in the anaerobic digestion of crude glycerol, the main by-product of the biodiesel industry. Fe3O4 nanoparticles were synthesized by the coprecipitation method and Scanning Electron Microscopy (SEM) characterized it. The method designed for synthesis produced stable Fe3O4 nanoparticles with diameters about 20 nm. Duplicate of anaerobic batch reactors (500 mL) were used for assessing the influence of Fe3O4 nanoparticles in four assays performed at 37 °C. The reactors were filled with anaerobic granular sludge; crude glycerol (25.0 g COD L−1); buffer solution; citrate-coated Fe3O4 nanoparticles suspension (0.2 g L−1; 0.4 g L−1 and; 0.8 g L−1 and a control without Fe3O4 nanoparticles); deionized water up to 250 mL. There were increases of 49.8%, 28.5% and 26.0% in the accumulated production of CH4 and 25.7%, 17.1% and 20.0% in the maximum rate of CH4 production in assays supplemented with 0.2, 0.4 and 0.8 g L−1 of Fe3O4 nanoparticles, respectively, in relation to control reactors. It was also observed a substantial increase on relative abundance of Bacteria and Archaea Domains, specially Bacteroides, Clostridiales, Methanomicrobiales and Methanosarcinales orders, after anaerobic digestion supplemented with Fe3O4 nanoparticles. The addition of Fe3O4 nanoparticles could improve the anaerobic digestion of crude glycerol, optimizing bacterial and archaeal communities enhancing the CH4 production.
Keywords: Anaerobic consortium; Biodiesel; Biofuel; Methane